STRATEGI HARGA DAN PROMOSI YANG DILAKUKAN E- COMMERCE DALAM MENINGKATKAN KEPUTUSAN PEMBELIAN KONSUMEN - Presly Darmawan (STIE Wiyatamandala, 2022)
The purpose of this study aims to analyze the effect of price, promotion on purchasing decisions in e-commerce. The analytical method used by the author inconducting this research is to use quantitative research involving 100 respondents in the city of Tangerang who have shopped at online stores. In collecting the data, it was done by distributing questionnaires in which there were several statements. In this study, the variables were divided into several parts, including price (X1), promotion (X2) as the independent variable, and purchasing decisions (Y) as the dependent variable. To measure the magnitude of the influence on these variables, the authors use multiple regression analysis method. From the results of the analysis, it is found that there is a significant and simultaneous influence on the price and promotion variables on purchasing decisions.